Macroeconomic theory : Keynesian and Neo-Walrasian models - Sawyer, John A. (New York ; London : Harvester Wheatsheaf; 1989., 2010)
"This volume focuses on current issues of debate in the area of modern macroeconomics and money, written from (a broadly interpreted) post Keynesian perspective. The papers connect with Philip Arestis' contributions to macroeconomics and money, and pay tribute to his distinguished career"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Macroeconomics; Capital market; Monetary policy